A new species of Terebellides (Polychaeta: Trichobranchidae) from Scottish waters with an insight into branchial morphology. - Parapar, J., J. Moreira & M. O'Reilly (Marine Biodiversity, 2016)
Based on specimens collected during several sampling programmes mainly in the northern North Sea, Scotland, a new species of the genus Terebellides (Polychaeta; Trichobranchidae) was found and described herein as Terebellides shetlandica spec. nov. The new species is primarily characterised by the presence of a long pointed posterior filament in the ventral branchial lobes. The species is compared with other Terebellides species described or reported from North Atlantic waters, and an updated key to the Terebellides species of the North East Atlantic and Mediterranean Sea is provided. The presence of copepods of the genus Melinnacheres attached to the thorax of this species is reported. Morphology of T. shetlandica spec. nov. was also studied with SEM and micro-CT. Branchial characters used in the taxonomy of the genus are reviewed and four general branchial types are defined.
World Polychaeta Database (WPolyDb)